Assessment of the lipid metabolic profile in sows supplemented with Lactobacillus casei during a reproductive cycle - Suárez Mesa, Rafael Antonio (2018)
A stable microbiota can act as an effective barrier against pathogen colonization besides to the production of metabolic substrates (e.g. vitamins, enzymes) and stimulate the mucosal immunity. Supplementation with probiotics have shown to improve the digestibility in pigs and work as an immunostimulant. The aim of this study was to assess the lipid metabolic profile in sows supplemented with Lactobacillus casei throughout a complete reproductive cycle. Eighteen F1 Landrace x Large White sows were randomly distributed in three experimental groups: control, T1 supplemented with 10 x 106 CFU (colony forming units)/g of L. casei and T2 supplemented with 10 x108 CFU/g of L. casei, administered weekly by oral route for 180 days, covering a reproductive cycle. Metabolites from lipid metabolic, hematic and protein profiles were analyzed in each sow at the day of service, 80-day and 113-day of pregnancy, 1st and 10th day postpartum and at 21 days of lactation (weaning age). At the peripartum period, differences were found in the levels of triglycerides and blood urea nitrogen (BUN), T1 and T2 showed higher values of triglycerides (p<0.05) and lower concentration of BUN (p<0.01) than the control group. At weaning time, T1 and T2 showed lower values of triglycerides and low-density lipoprotein (p<0.05) than control group. Sows in pregnancy and lactation period supplemented with L. casei showed higher levels of triglycerides and cholesterol than those without supplementation. In addition, probiotic supplementation did not induce changes in high-density lipoprotein, total protein, and albumin levels. All these changes may have positive metabolic effects for the sows, nevertheless, further studies are required to elucidate the role of the supplementation with probiotics on the metabolic profile.